Factors associated with postnatal care for newborns in Zambia: analysis of the 2013-14 Zambia demographic and health survey - Bupe B. Bwalya; Mulenga C. Mulenga; James N. Mulenga (BMC, 2017)
Abstract Background The importance of postnatal care cannot be overemphasised. Various studies undertaken worldwide have found that PNC is critical for the survival of newborns. However, in Zambia, despite much emphasis by the government and various international Organisations on the need for PNC, coverage continues to be low. This study attempted to assess the demographic and socio-economic factors associated with newborns' receipt of PNC and the timing of first PNC in Zambia. Methods Based on data from the 2013-14 Zambia Demographic and Health Survey (ZDHS), this study used bivariate, stepwise binary and multinomial logistic regression analyses to examine PNC for births at home and at health facilities. Results The results indicate that different factors influence the utilisation of PNC among home births, these include: place of delivery, mothers' exposure or access to media and having 4+ ANC visits. On the other hand, place of residence and mothers' access or exposure to media were found to be the determinants of PNC among facility deliveries. The results further indicate that among the home births, mothers' media exposure or access to media, having secondary or higher education, and having 4+ ANC visits during pregnancy increased the odds of having PNC within 48 hours. Furthermore, attending the first PNC 48 hours after delivery was determined by place of residence, media exposure and 4+ ANC visits. On the other hand, among the facility births, the timing of PNC within 48 hours, was influenced by the perceived size at birth of the newborn. Conclusion The study makes the following recommendations: more attention to be given to rural based women and newborns; encourage delivery at health facilities; more emphasis on the importance of ANC visits; and need to disseminate information through various media on the importance of PNC even in rural communities.